The Concept of Safe Zakat Management According to the Provisions of the Prevailing Laws and Regulations in Indonesia - Hendar, Jejen; Ruhaeni, Neni; Zakiran, Asep Hakim (KnE Social Sciences, 2023)
Poverty remains an inherent reality in the lives of Indonesian people, largely due to the prolonged economic downturn faced by the nation. This issue is prevalent in developing countries, including Indonesia, affecting a significant portion of its population. To address this challenge, Allah Almighty has established zakat, infak, and alms, encouraging financially capable Muslims to show compassion for the poor and fostering a harmonious relationship between the two. The purpose of this study is to explore the concept of safe zakat management, ensuring compliance with prevailing laws and regulations in Indonesia. The article adopts the normative juridical method with a normative sociological approach, relying on secondary data sources and employing analytical descriptive methods for analysis. To tackle poverty effectively, cooperation with both government and private institutions, known for their proficient financial management, is crucial. This collaboration serves as an effort to overcome these social problems. In managing zakat, there are specific rules that govern both positive law and Islamic law. It is essential for this management to align with applicable regulations and the provisions of Islamic law. Through such efforts, the public can gain a comprehensive understanding of how to manage zakat safely and in accordance with the relevant regulations, ensuring it is halal (permissible) in line with Islamic principles. Keywords: zakat management, zakat, safe